P 15 Long-term subthalamic deep brain stimulation modulates pathological beta oscillations in the AAV-A53T-Synuclein Parkinson's disease rat model. (May 2022) - Chen, J.Z.; Hofman, K.; Koprich, J.B.; Brotchie, J.M.; Volkmann, J.; Ip, C.W.
Abstract : Introduction: Aberrant beta (13-35 Hz) synchrony within the cortico-basal ganglia circuit has been reported as disease-specific hallmark of human Parkinson's disease (PD). The suppression of pathologically enhanced beta oscillations following subthalamic deep brain stimulation (STN-DBS ) is considered to be a crucial mechanism mediating improved motor function in PD patients and animal models. However, it remains unclear how long-term STN-DBS modulates beta oscillations over time in PD models with ongoing dopaminergic neurodegeneration. To clarify, we performed 3 weeks of continuous STN-DBS in a pathologically-relevant preclinical AAV-A53T-αSynuclein PD rat model (A53T). This model is characterized by a gradual nigrostriatal degeneration and reflects clinical hallmarks of human PD, thus allowing us to study neuromodulatory effects of long -term STN-DBS. Materials & methods: In this study, adult male Sprague Dawley rats were randomly assigned to EV (Empty Vector) and A53T groups and additionally divided into 2 subgroups: stim-ON and stim-OFF. During stereotaxic injection of viral vectors (EV or human AAV-A53T-αSynuclein virus), electrophysiological recordings and DBS electrodes were implanted. To obtain the LFP and ECoG data, we conducted monopolar LFP recordings in globus pallidus - external segment (GPe) and electrocorticography (ECoG) in motor cortex during 4 recording sessions - 1, 3, 6, 8 weeks after surgery. Continuous high frequency DBS / sham-DBS was induced from the 3rd week on, lasting for additional 3 weeks. Neuromodulatory effects of long-term STN-DBS on LFP / ECoG were evaluated immediately at stimulation termination in awake, resting state animals, and repeated after wash-out period for 2 weeks. Results: Both A53T groups developed augmented beta activity in MCx and GPe vs. EV at week 3 after surgery (X 2  ≥7.33, p≤0.03; z≥-2.45, p≤0.05). In the A53T stim-ON group, 3 weeks of continuous STN-DBS suppressed the elevated MCx and GPe beta power compared to EV at week 6 (z≥-1.12, p≥0.25). Specifically, in the A53T stim-ON group, the suppressive effect of beta power after the long-term STN-DBS was still present after 2 weeks wash-out period in the GPe (z = -1.41, p = 0.16), but not in the MCx (z = -2.12, p = 0.03) compared to EV. In contrast, the A53T stim-OFF group augmented MCx and GPe beta power sustainably for 8 weeks (z≥-2.45, p≤0.05). Conclusion: Our preliminary results suggest that long-term STN-DBS has a suppressive effect on pathological beta oscillations in the progressive A53T-aSyn PD rat model.